Formation of students’ critical thinking in the process of teaching chemistry - Kokibasova, G.T.; Serikova, K.K.; Abisheva, M.M. (Вестник Карагандинского университета, 2016)
Acquired in the process of Chemistry learning knowledge, skills, achieved development of critical thinking should help students to adapt to the realities of modern life. The main condition for the development of criti- cal thinking is not a presentation of a specific and limited amount of information, but motivation of interest in the Chemistry study, the critical assessment of the proposed theoretical and empirical material by students and then synthesizing them in their activities. The article contains the analysis of pedagogical experiment, where it was established a level of formation of students' critical thinking, as well as a description of some of the techniques and strategies that can be applied in the chemistry lessons.
Keywords: critical thinking; techniques and strategies; insert; reflection